2022
DOI: 10.1186/s40001-022-00870-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum homocysteine, fibrinogen, lipoprotein-a level, and peripheral arterial disease: a dose–response meta-analysis

Abstract: Aim At present, the relationship between serum homocysteine (Hcy), fibrinogen (FIB), lipoprotein-a (LPa), and PAD is uncertain, and there has been no meta-analysis to establish the dose–response relationship between their exposure levels and PAD. Methods and results Relevant literature published in PubMed, Embase, and Web of Science was retrieved. The robust error meta-regression method was used to assess the linear and non-linear dose–response rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 98 publications
2
5
0
Order By: Relevance
“… 19 Moreover, a multi‐population meta‐analysis of 11 687 patients showed higher plasma Hcy levels in patients with PAD compared with healthy individuals. 28 Consistent with the conclusions of our study, these studies all showed a significant association between plasma Hcy and PAD. However, Ridker and coworkers did not find a clear association between plasma Hcy and PAD in a nested case‐control study of 240 United States male physicians.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 19 Moreover, a multi‐population meta‐analysis of 11 687 patients showed higher plasma Hcy levels in patients with PAD compared with healthy individuals. 28 Consistent with the conclusions of our study, these studies all showed a significant association between plasma Hcy and PAD. However, Ridker and coworkers did not find a clear association between plasma Hcy and PAD in a nested case‐control study of 240 United States male physicians.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a case‐control study by Rong and coworkers also showed a higher risk of PAD with high plasma Hcy levels in Chinese adults 19 . Moreover, a multi‐population meta‐analysis of 11 687 patients showed higher plasma Hcy levels in patients with PAD compared with healthy individuals 28 . Consistent with the conclusions of our study, these studies all showed a significant association between plasma Hcy and PAD.…”
Section: Discussionsupporting
confidence: 91%
“…It has been provided that elevated Hcy may raise the risk of Peripheral Artery Disease (PAD). Well controlling the level of Hcy could potentially reduce the incidence of PAD and help address the growing epidemic of PAD [9]. Furthermore, the increased total Hcy level has been categorized as a contributing factor to borderline Ankle-Brachial Index (ABI).…”
Section: Discussionmentioning
confidence: 99%
“…HHcy is a disorder involving a wide variety of diseases, it arises when the metabolism of Hcy is disrupted due to deficiencies in B-vitamins, genetic defects, or other pathophysiological conditions [5,6]. HHcy have been convincingly linked to cardiovascular, cerebrovascular, neurodegenerative, and thromboembolic diseases, and also been found to have a close relationship with peripheral artery diseases [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Lp(a) is a form of a low-density lipoprotein (LDL) and is an established and genetically determined risk factor for atherosclerosis, coronary artery disease (CAD), stroke, and aortic stenosis [ 1 , 2 ]. Moreover, high plasma levels of Lp(a) nearly double the risk of developing peripheral artery disease [ 3 ]. Mendelian studies also associate a high Lp(a) with a mildly though significantly higher risk of developing atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%